2018
DOI: 10.4194/1303-2712-v18_9_02
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: A 60-day feeding trial was conducted to study the nutrient utilization and growth performance of Labeo rohita fed with T1 [DORB supplemented with phytase and xylanase (0.01% each)], T2 [ T1+ L-lysine(1.4%), L-methionine (0.4%), combination of EPA and DHA (0.5%)] , T3 [DORB supplemented with phytase (0.01%), combination of xylanase and cellulase (0.075%), L-lysine (1.4 %), L-methionine (0.4 %), combination of EPA and DHA (0.5%)] and T4 (commercially available carp feed) diets. Weight gain%, SGR, and FCR were si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 50 publications
2
3
0
Order By: Relevance
“…Since exogenous NSPase could improve the crude fibre digestion and lead to more amount of soluble carbohydrate in the intestine, it might have stimulated the pancreas for release of more amylase (Li et al, 2009). In corroboration with the present finding, Ranjan et al (2019) observed improved dry matter digestibility of DORB-based diet in fish due to supplementation of exogenous enzymes. Moreover, in agreement with our observation, Shi et al (2017) reported that supplementation of carbohydrases at 1 g/kg diet of crucian carp (Carassius auratus) did not affect ACPDC and ALDC.…”
Section: Catalasesupporting
confidence: 90%
See 3 more Smart Citations
“…Since exogenous NSPase could improve the crude fibre digestion and lead to more amount of soluble carbohydrate in the intestine, it might have stimulated the pancreas for release of more amylase (Li et al, 2009). In corroboration with the present finding, Ranjan et al (2019) observed improved dry matter digestibility of DORB-based diet in fish due to supplementation of exogenous enzymes. Moreover, in agreement with our observation, Shi et al (2017) reported that supplementation of carbohydrases at 1 g/kg diet of crucian carp (Carassius auratus) did not affect ACPDC and ALDC.…”
Section: Catalasesupporting
confidence: 90%
“…the negative effect of the ANFs present in PSLM. Moreover, in the present study, dietary supplementation of exogenous cellulase and xylanase mixture at 1 g/kg in low PSLM group (150 g PSLM/kg) significantly improved the whole-body protein content, while fish fed with exogenous enzyme and supplemented with high PSLM (300 g PSLM/kg) could not show a significant difference of whole-body protein content compared to their non-supplemented counterparts.In agreement with the present observation,Ranjan et al (2019) reported that carcass protein content of L. rohita fed with DORB-based diets was not altered due to dietary addition of NSP degrading enzymes. However, in contrast to our finding,Ai et al (2007) reported that supplementation of NSP degrading enzyme in plant-based diet could enhance the carcass protein content in Japanese seabass.…”
supporting
confidence: 93%
See 2 more Smart Citations
“…DORB contains 15-17% crude protein and 12-16% crude fibre (Ranjan et al, 2017). As DORB is widely distributed, easily available and cheapest, it is most commonly incorporated in fish farm-made feed along with different oilcakes (Meshram et al, 2018;Ranjan et al, 2017Ranjan et al, , 2018Ranjan et al, , 2019. However, recent studies indicated that 33-40% inclusion of DORB in the carp diet does not affect the growth in rohu fingerlings (Kumar et al, , 2019.…”
mentioning
confidence: 99%